(untitled) (Journal of Open Law, Technology & Society, 2011)
The IT sector is characterized by two market failures, the “tragedy of the commons” and the “tragedy of the anti-commons”, both of which must be resolved if IT innovation is to flourish and lock-in avoided. This involves a careful balancing of IPR protection and standard- setting, while avoiding hold-up and preserving opportunities for the significant innovation provided by the open source movement. The Author examines the shortcomings of the present system from a European Law perspective and expresses a plea for Open Standards in the interest of innovation and technological progress. As IT progresses, more and more products are compound items, incorporating technology co-owned by many different patent holders, co-manufactured by different producers, and interoperating with other complex products. A hold-up by a non-practicing entity or a rival using a single patent on a single component can kill an entire product. This article explores the criteria for “open standards”, and explains why royalty-free licensing of interoperability standards is appropriate in the software area (since RF standards can be implemented in both open source and proprietary software, thus allowing both models to compete on quality and functionality), while FRAND licensing is necessary for telecommunications. The notion of FRAND terms is further explored from a legal and economic perspective, explaining ways to determine fair pricing, and the need to ensure non- discriminatory terms in order to preserve competition in products implementing the standard. The article concludes with some comments on an interesting report by RAND Europe on “Trends in Connectivity Technologies and their Socio-Economic Impacts – Policy Options for the Ubiquitous Internet Society”.